Rehabilitation outcome and socioeconomic inequality - a preliminary study in Slovenia - Vidmar, Gaj (Informatica Medica Slovenica, 2012)
Though inequality in health has lately been extensively studied in Slovenia, the possible association of rehabilitation outcome with socioeconomic inequality has not been previously explored. The data on all adult inpatients discharged from the University Rehabilitation Institute in Ljubljana in a year were analysed. Seven categorical variables were available: the binary outcome (achievement of functional independence), basic demographic and medical characteristics, and insurance type (as a proxy for socioeconomic status). Multiple logistic regression, classification tree (CHAID) and Bayesian dependence modelling were applied. All analyses corroborated the relevance of insurance type as predictor of rehabilitation outcome. In further work, we will update and extend the dataset and apply more sophisticated statistical methods.
Keywords: izid zdravljenja; rehabilitacija; rehabilitation; rehabilitation outcome; Slovenia; Slovenija; socioeconomic inequality; socioekonomska neenakost; University Rehabilitation Institute, Republic of Slovenia; Univerzitetni rehabilitacijski inštitu Republike Slovenije - Soča